GREEN GROWTH, JUST TRANSITION AND DECENT WORKS IN THE CONTEXT OF SUSTAINABLE DEVELOPMENT AND COMBATTING CLIMATE CHANGE - Çiğdem Tuğaç (Alternatif Politika)
Traditional economic growth models damage natural resources to which humanity depends, causing important environmental, social and economic problems, especially climate change. Today, it is understood by countries that a new growth approach should be applied in order to ensure the sustainable use of scarce natural resources, combatting negative effects of climate change and reduce poverty while realizing economic development. The view that environmentally friendly investments aren’t cost effective is changing and countries want to take advantage of the opportunities offered by green growth. However, this process also requires a just transition. The aim of this study is to evaluate green growth, just transition and decent work concepts in the context of sustainable development and combatting climate change. In the study, it is concluded that if green growth and just transition processes are well managed, they provide significant opportunities for realizing UN-SDGs, combatting climate change and the creation of decent works.